Current and future state of the management of Hirschsprung disease - Jessica L Mueller; Ryo Hotta (World Journal of Pediatric Surgery)
The enteric nervous system (ENS) consists of a network of neurons and glia that control numerous complex functions of the gastrointestinal tract. Hirschsprung disease (HSCR) is a congenital disorder characterized by the absence of ENS along variable lengths of distal intestine due to failure of neural crest-derived cells to colonize the distal intestine during embryonic development. A patient with HSCR usually presents with severe constipation in the neonatal period and is diagnosed by rectal suction biopsy, followed by pull-through procedure to surgically remove the affected segment and reconnect the proximal ganglionated intestine to the anus. Outcomes after pull-through surgery are suboptimal and many patients suffer from ongoing issues of dysmotility and bowel dysfunction, suggesting there is room for optimizing the management of this disease. This review focuses on discussing the recent advances to better understand HSCR and leverage them for more accurate and potentially less invasive diagnosis. We also discuss the potential future management of HSCR, particularly cell-based approaches for the treatment of HSCR.